2021
DOI: 10.1002/wcms.1518
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in organocatalysis—From qualitative to quantitative predictive models

Abstract: Recent advances in both experimental and computational techniques pose an exciting time for chemistry. Computational tools traditionally used to interpret experimental trends have now evolved into predictive models able to guide the design of novel catalysts. This review discusses the evolution of these models, as well as challenges and future avenues in the field of organocatalysis. Through representative examples we demonstrate how traditional physical organic chemistry tools in combination with machine lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…After conformation analysis of the peptide catalyst based on Miller’s pioneering studies on β -turn-containing tetrapeptides 62 , 63 , it was found that the approach of the radical adduct in the transition state (TS) is dictated by the C=O ··· H–N interaction in the backbone (highlighted with blue dash lines). Moreover, the Si and Re faces of the carbon radical interact differently with the peptidic thiol in the transition states due to non-covalent dispersion interactions 64 , 65 , with TS- Si displaying strong C–H ··· π interactions between the proline and the phenyl ring of the radical adduct. In contrast, only weak C−H ··· π interactions are identified in TS- Re .…”
Section: Resultsmentioning
confidence: 99%
“…After conformation analysis of the peptide catalyst based on Miller’s pioneering studies on β -turn-containing tetrapeptides 62 , 63 , it was found that the approach of the radical adduct in the transition state (TS) is dictated by the C=O ··· H–N interaction in the backbone (highlighted with blue dash lines). Moreover, the Si and Re faces of the carbon radical interact differently with the peptidic thiol in the transition states due to non-covalent dispersion interactions 64 , 65 , with TS- Si displaying strong C–H ··· π interactions between the proline and the phenyl ring of the radical adduct. In contrast, only weak C−H ··· π interactions are identified in TS- Re .…”
Section: Resultsmentioning
confidence: 99%
“…Although useful for the rationalization and prediction of absolute stereochemistry, the simultaneous analysis of multiple stereochemical models may limit the application. Further, simple models that can be sketched by hand are qualitative and do not provide a quantitative prediction of the enantioselectivity output . Accordingly, we deployed statistical modeling tools, which could greatly enhance the application and predictive power of our reaction models. To connect these nine disparate reaction types, a comprehensive multivariate linear regression (cMLR) model that relates the features of all of the reaction components to the experimentally obtained enantioselectivity outcomes conveyed as ΔΔ G ‡ would be required (see SI for full details on workflow, statistical models considered, and additional validation tests) .…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to physics, chemistry rarely has known theoretical models, and chemists usually work using their own intuition and empirical evidence. Based on this, chemists have developed the field of "chemoinformatics" where machine learning has been used extensively [18], [19], and recently generative architectures similar to the ones developed in this work have also been used [20]- [22]. The main difference in this work is that we did not aim to predict synthesizability, but we focused instead on tracking real-time experimental changes based on user-input.…”
Section: Related Workmentioning
confidence: 99%